ANALYSIS OF AGRITOURISM AND RURAL TOURISM SITUATION IN THE NORTH EAST OF ROMANIA - Maria STOIAN; Alina MĂRCUȚĂ; Ioana NICULAE; Liviu MĂRCUȚĂ (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
One has determined that the successful formation and development of the market of agricultural lands depends on a combination of various factors, taking into consideration the successful development of the agrarian sector of the economy as a whole. One has considered all external and internal factors affecting the development of the market of agricultural lands. One has systematized these factors into four large groups: environmental, economic, social and legal ones. Ecological factors include the composition and type of soil, the level of contamination and the land user’s environmental policy. Economic factors affect the price of land plot depending on its size and form, geographical location of the land plot, competition on the market and infrastructure development. The social group includes all factors that are in some ways connected with the social sphere. Legal factors are related to the relationship of the state, economic entities, and the population. One has revealed that the major component of the conceptual essence of the market is a market mechanism, which is a method of interaction between the seller and the buyer, based on demand, supply and price. One has substantiated that the long-term lease of agricultural lands will be the instrument of effective market development.